2020
DOI: 10.1371/journal.pone.0227573
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among patients with type 2 diabetes mellitus in Eastern Province, Saudi Arabia: A cross-sectional study

Abstract: Diabetes mellitus has reached epidemic levels, and it threatens the economy and health globally and Saudi Arabia in particular. The study assessed health-related quality of life using EuroQol instrument and its predictors among patients with Type 2 diabetes mellitus in Eastern Province, Saudi Arabia. A cross-sectional study was conducted among 378 patients with Type 2 diabetes mellitus from two major health centers in Eastern Province. The study showed moderate health-related quality of life, as reported by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
77
2
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 36 publications
23
77
2
3
Order By: Relevance
“…The percentage of individuals reporting problems in each of the EQ-5D dimensions showed that pain and mobility were the most common problems among subjects. This pattern was similar to those reported recently in a local survey in Birjand, Iran, 11 and the surveys conducted in Saudi Arabia 38 and Jordan. 28 The results of the difference in HRQoL score in each factor and effective factors on HRQoL are discussed in two separate groups: demographic and clinical factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The percentage of individuals reporting problems in each of the EQ-5D dimensions showed that pain and mobility were the most common problems among subjects. This pattern was similar to those reported recently in a local survey in Birjand, Iran, 11 and the surveys conducted in Saudi Arabia 38 and Jordan. 28 The results of the difference in HRQoL score in each factor and effective factors on HRQoL are discussed in two separate groups: demographic and clinical factors.…”
Section: Discussionsupporting
confidence: 92%
“…Studies carried out on the HRQoL of the patients with T2DM often found that mean HRQoL of male was higher than that of the female patients. 11,14,28,38 These findings were observed in our study. The main reason for higher HRQoL in men compared to women is the higher level of physical activity in men in developing countries like Iran, as shown in a systematic review on physical activity.…”
Section: Discussionsupporting
confidence: 89%
“…In China, the QoL scale was developed for diabetic patients in 1997, which measured the four dimensions of life, heart, society, and treatment; in 2005, a special tool was used for evaluating the QoL of diabetic patients, which is developed from the dimensions of disease, physiology, psychology, society, and satisfaction in 87 items; Fu et al (2010) simplified the QoL scale of 2005, from 87 items to 39 items according to Chinese national conditions, and made it more effective and kept its dimension unchanged. A large number of studies have shown that the QoL of patients with T2DM is significantly lower than that of healthy people ( Schulze and Hu, 2005 ; Alshayban and Royes, 2020 ). PA has closed relationship with QoL ( Nana et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous study, more males were involved in physical activities compared to females, particularly in developing countries such as Bangladesh and Arab countries. In some countries, females were mostly staying at home as housewives (Alshayban & Joseph, 2020;Al-Aboudi, Hassali, & Shafie, 2016). Other demographic factors that contributed to poor behaviour, such as level of education, marital status and duration of disease (Al-Maskari et al, 2013).…”
Section: Behaviourmentioning
confidence: 99%